Analisis Suku Bunga Pasar Uang Antar Bank pada Variabel Makroekonomi di Indonesia - Prawesti, Regina Wintang; Kusumahadi, Teresia Angelia (Jurnal Cita Ekonomika, 2025)
This study examines the impact of the Interbank Money Market Rate (PUAB) on macroeconomic variables in Indonesia, specifically the exchange rate, real output, and inflation, from 2005 to 2022. Using the Vector Error Correction Model (VECM) method, this research finds that the PUAB rate significantly impacts all three variables. The estimation results indicate that the PUAB rate has a significantly positive effect on the exchange rate in both the short and long term, where an increase in the PUAB rate leads to currency depreciation. Additionally, the PUAB rate negatively impacts real output and inflation, which is consistent with the monetary policy objective of maintaining price stability. These findings confirm the PUAB rate's effectiveness as a monetary policy instrument in achieving final targets, although the time required to reach the desired outcomes may vary.